Factors Affecting Nurse Performance at Datu Beru Takengon General Hospital - Mappeaty Nyorong; Asyiah Simanjorang; Jauhari Jauhari (Journal La Medihealtico, 2021)
This study aims to determine the factors that influence the performance of nurses and to determine the most dominant factors affecting the performance of nurses at the General Hospital Datu Beru Takengon 2021. The research design used a quantitative analytic survey with a cross-sectional design. The population is all nurses in the Inpatient Room at RSU Datu Beru Takengon as many as 200 people. The sampling technique used was random sampling. Data analysis was performed by univariate, bivariate and multivariate analysis with chi_square. The results of the Chi-Square statistical test analysis obtained p-value = 0.003 < 0.05, which means there is a relationship between workload and nurse performance, while the length of service period obtained p-value = 0.652 < 0.05, which means there is no relationship between length of service and nurse performance, the training variable obtained p-value = 0.004 < 0.05 which means there is a relationship between training and nurse performance, the discipline variable obtained p-value = 0.005 < 0.05 which means it means that there is a relationship between discipline and nurse performance and the motivation variable is obtained p-value = 0.002 < 0.05, which means there is a relationship between motivation and nurse performance. The results of the Multivariate test analysis showed that the variables that influenced the performance of nurses were workload, discipline and motivation, while the most dominant variable was the workload variable with p = 0.002 <0.05.